Morbidities Worsening Index to Sleep in the Older Adults During COVID-19 - Almondes, Katie Moraes de (2022)
Funding Information: This study was supported by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior-Brasil (CAPES)-Finance Code 001. Publisher Copyright: Copyright © 2022 Almondes, Castro and Paiva.